Enhanced sunlight-driven photocatalytic activity of graphene oxide/Bi2WO6 nanoplates by silicon modification. Issue 8 (September 2015) - Xiao, Yi; Chen, Chuansheng; Cao, Shiyi; Qian, Guoping; Nie, Xiaobao; Yu, Weiwei
Abstract: In order to improve the photocatalytic activity and reduce the cost of graphene oxide/Bi2 WO6 (GO/BWO) nanohybrids for practical application, silicon-modified graphene oxide/Bi2 WO6 (Si-GO/BWO) nanoplates were successfully prepared by a facile one-pot hydrothermal method. X-ray diffraction and BET study of the products reveal that the incorporation of Si atoms can greatly alter the microstructure of GO/BWO composite with enlarged specific surface area. The UV–vis diffuse reflectance spectra indicate that the obtained Si-GO/BWO nanoplates have enhanced absorption in both UV and visible light regions. The Si–GO/BWO nanocomposite shows increased photocatalytic activity on the degradation of high concentration RhB solution under visible light irradiation and simultaneously keeps a very high stability, due to the good textural properties. In addition, the incorporation of Si with a load of 19.3 wt% could greatly reduce the cost of BWO based photocatalyst.